Evaluation of Starch From New Sweet Potato Genotypes for use as A Pharmaceutical Diluent, Binder or Disintegrant - Marcel Tunkumgnen Bayor, Eric Tuffour, Paul Salo Lambon (Journal of Applied Pharmaceutical Science, 2013)
Starches from four new sweet potato genotypes were evaluate for use as tablet diluents, binders and disintegrants; using a commercially available maize starch as reference. The pre-formulation studies established low pH (5.1 - 5.9) and moisture content (10.0 - 13.1%), but high bulk density (0.50 - 0.58), tapped density (0.75 - 0.82) and true density (1.15 - 1.18) for the sweet potato starches. Hardness and friability of tablets formulated with sweet potato starches as binder were significantly better (p = 0.001) than similar compacts containing maize starch. The sweet potato starches also caused significantly faster tablet disintegration and release of paracetamol (p = 0.005). The results established the sweet potato starches as stronger pharmaceutical diluents, binders and disintegrants, compared to the commercially available maize starch.
Keywords: Sweet potato, genotype, starch, excipient, diluent